Pengaruh Koneksi Politik Terhadap Praktik Manajemen Laba Riil Pada Perusahaan Manufaktur di Indonesia - Supatmi Supatmi; Indriyani Dwi Putri (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to analyze the effect of political connections on earnings management practices in manufacturing companies. The sample of this study was 153 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period with a total of 459 observations. Earnings management in this study was measured by real earnings management, namely abnormal CFO, abnormal discretionary expense, and abnormal production. Political connection is measured by the number of boards in the company, both the board of directors and the board of commissioners, who are politically connected. The research hypotheses were tested using panel data regression analysis techniques. The results showed that the politically connected board of commissioners has a positive effect on earnings management as measured by abnormal discretionary expense and a negative effect through the measurement of abnormal production. Politically connected board of commissioners has no effect on earnings management through abnormal measurement of CFO. Meanwhile, the politically connected board of directors was found to have no effect on earnings management, either by measuring abnormal CFO, abnormal discretionary expense, or abnormal production. The research findings confirm the application of agency theory that political connections within the company, especially politically connected boards, affect the company's earnings management practices